2006
DOI: 10.1073/pnas.0602815103
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the bacterial polysaccharide antigenicity ofStreptococcus agalactiaeversusStreptococcus pneumoniae

Abstract: Bacterial surface capsular polysaccharides (CPS) that are similar in carbohydrate sequence may differ markedly in immunogenicity and antigenicity. The structural origin of these phenomena is poorly understood. Such a case is presented by the Gram-positive bacteria Streptococcus agalactiae (Group B Streptococcus; GBS) type III (GBSIII) and Streptococcus pneumoniae (Pn) type 14 (Pn14), which share closely related CPS sequences. Nevertheless, antibodies (Abs) against GBSIII rarely cross-react with the CPS from Pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 43 publications
0
45
1
Order By: Relevance
“…29 A model for HA 8 was generated by setting the glycosidic (φ,ψ) angles for each linkage (Supplemental Figure 1, see Supplementary material) to the most representative values from the MD data (Supplemental Table 1, see Supplementary material). For ligand docking, a fragment-based docking protocol previously described 30 was modified by employing the rigid whole-molecule docking approach. This modification was adopted because of the large numbers of degrees of freedom present in highly flexible molecules, and the associated potential energy convergence problems.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…29 A model for HA 8 was generated by setting the glycosidic (φ,ψ) angles for each linkage (Supplemental Figure 1, see Supplementary material) to the most representative values from the MD data (Supplemental Table 1, see Supplementary material). For ligand docking, a fragment-based docking protocol previously described 30 was modified by employing the rigid whole-molecule docking approach. This modification was adopted because of the large numbers of degrees of freedom present in highly flexible molecules, and the associated potential energy convergence problems.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Such enthalpy-entropy compensation has been reported for many antibody-carbohydrate interactions (8,12). The serotype 14 PS is an uncharged polymer and is highly conformationally mobile (20). Despite the conformational flexibility of the serotype 14 PS, a conformational epitope consisting of at least four repeating units has been proposed for the serotype 14 PS (21, 45).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the spacing of the binding of the Fabs along the PS calculated from these studies, about 3 nm per bound Fab at saturation, is relatively consistent with published estimates of the size of an antibody binding site (19) and with estimates of the dimensions of an Fab fragment (30,31,35,42), suggesting that anti-PS antibodies of moderately high affinities are capable of binding as densely along the PS chain as permitted by steric interactions between the IgG molecules and may therefore recognize structural or linear epitopes rather than conformational epitopes. Recognition of immunodominant and functionally important conformational epitopes by polyclonal antibodies and MAbs has been proposed for the group B streptococcal type III PS (7,46), the serotype 14 PS (20,21,45), and the Neisseria meningitidis serogroup B PS (6,11,23,24). In contrast, there is evidence to suggest that conformational epitopes may not be present or may not play an important role in generating functional immune responses for serotype 3, 6A, 18C, 19F, or 23F PS (22) or pneumococcal serogroup 9 capsular PS (32,33).…”
mentioning
confidence: 99%
“…Native Pn14PS is structurally related to and has cross-reactivity with GBSIIIPS [81]. The branched structures of Pn14PS and GBSIIIPS differ only in the absence (in Pn14PS) or presence (in GBSIIIPS) of the ( 23)-linked sialic acid N-acetylneuraminic acid (Neu5Ac) in their side chains: [82]. We reported that type-specific Pn14PS antibodies which recognize the branched structure of Pn14PS have a low affinity for the native GBSIIIPS and do not promote opsonophagocytosis of GBSIII, however desialylation of GBSIIIPS, however, resulted in dramatically higher affinity of anti-Pn14PS antibodies in mice when GBSIIIP was treated by nurimindase (desialylation) [80].…”
Section: Relationship Between Polysaccharide Of Pn14ps and Gbsiiimentioning
confidence: 99%